Pressure injury prevalence in critical care settings: An observational pre‐post intervention study - Bassam Alshahrani; Rebekkah Middleton; Kaye Rolls; Jenny Sim (Wiley, 2024)
Abstract Aim To explore pressure injury prevention practices and evaluate the impact of an educational intervention on PI prevalence before and after an educational intervention. Design A multi‐centre observational study. Method Data were collected at two time points in May 2021 and April 2022 using a Qualtrics® online form. Two Registered Nurses at each site collected observational data at each time point by diagnosing and staging any identified pressure injuries as part of a prevalence study. Patients admitted to participating units were included. Results A total of 181 patients in critical care units were included at the two‐time points. Pressure injury prevalence was 60.9% at the outset, with 52.9% hospital‐acquired, 37.9% unit‐acquired and 23.0% medical device‐related. Post‐intervention prevalence decreased significantly to 28.7%, including 21.3% hospital‐acquired, 14.9% unit‐acquired, and 8.5% medical device‐related. Pressure injuries were prominent in the sacral region, head area, and heels. Stages I and II pressure injuries were the most common. Increased age and longer ICU stays are linked to a heightened risk of pressure injury development in critically ill patients, whereas higher haemoglobin levels show an inverse relationship with the development of both pressure injury and severe stages in the univariate analysis. The predictive models revealed that increased age and longer ICU stays are predictors for both pressure injury development and progression to severe stages, while Braden scores predict the likelihood of developing severe stages of pressure injuries. Conclusions This study has identified a benchmark for pressure injury prevalence in critical care units in Saudi Arabia. The results demonstrate that pressure injuries can be prevented in critically ill patients when evidence‐based education strategies are implemented. Patient Care Impact Pressure injuries are an important issue for critically ill patients and can be prevented with proper investments. Strategies to prevent pressure injuries from admission will result in fewer pressure injuries. Reporting Method Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines and the Template for Intervention Description and Replication (TIDieR) checklist. Patient or Public Contribution No patient or public contribution.